Health Literacy-Related Knowledge, Attitude, and Perceived Barriers: A Cross-sectional Study among Physicians, Pharmacists, and Nurses in Public Hospitals of Penang, Malaysia - Rajah, Retha; Hassali, Mohamed Azmi; Lim, Ching Jou (Frontiers in Public Health, 2017)
Introduction: Patients' health literacy (HL) has emerged as a critical determinant of health outcomes and becoming one of the core competency of health care providers.Therefore, this study aimed to assess among Malaysian physicians, pharmacists and nurses, their HL related knowledge, attitude and perceived barriers, and also to determine the associated factors. Methods: A cross-sectional study design was used to enroll six hundred eligible respondents using stratified sampling from six public hospitals in Penang, Malaysia. A validated self-administered questionnaire was used for data collection. Descriptive and inferential analysis was performed with statistical significance defined as p < 0.05. Results: The response rate was 87.6% with 526 questionnaires completed. Of these, 34.2% had poor knowledge, and more than half had negative attitude (51.9%) towards HL with no significant differences among physicians, pharmacists, and nurses. The majority of the respondents perceived time constraints and lack of human resources as major HL barriers. Respondents who had heard the term or concept of HL had significantly higher level of knowledge (p<0.001) and more positive attitude (p<0.001). While longer service years (≥11 years) significantly contributes to the higher level of HL knowledge among healthcare providers (p=0.028). Conclusion: The study findings supported the concern on inadequate knowledge and substantially negative attitude towards HL among study healthcare providers with highest cited barriers were time constraint and human resources. Thus, efforts to improve their perspective about HL to be effective patient educators are highly advocated.